Genetic Characterization of the O-Antigen and Development of a Molecular Serotyping Scheme for Enterobacter cloacae - Li, Yayue; Huang, Junjie; Wang, Xiaotong; Xu, Cong; Han, Tao; Guo, Xi (Frontiers in Microbiology, 2020)
Enterobacter cloacae is a well-characterized opportunistic pathogen that is closely associated with various nosocomial infections. The O-antigen, which is one of the most variable constituents on the cell surface, has been used widely and traditionally for serological classification of many gram-negative bacteria. E. cloacae is divided into 30 serotypes, based on its O-antigen diversity. In this study, by using genomic and comparative-genomic approaches, we analyzed the O-antigen gene clusters of 26 E. cloacae serotypes in depth. We also identified the sero-specific gene for each serotype and developed a multiplex polymerase chain reaction method. The sensitivity of the assay was 0.1 ng for genomic DNA and 103 colony forming units for pure cultures. The assay reliability was evaluated by double-blinded testing with 81 clinical strains. Furthermore, we established a valid, genome-based tool for in silico serotyping of E. cloacae. By screening 431 E. cloacae genomes deposited in GenBank, 304 were classified into current antigenic scheme, and 112 were allocated into 55 putative novel serotypes. Our results represent the first genetic basis of the O-antigen diversity and variation of E. cloacae, providing a rationale for studying the O-antigen associated evolution and pathogenesis of this bacterium. In addition, we extended the current serotyping system for E. cloacae, which is important for detection and epidemiological surveillance purposes for this important pathogen.